Theta-Burst Stimulation of Forearm Muscles in Patients With Complex Regional Pain Syndrome: Influence on Brain and Clinical Outcomes - Allen Demers, Fannie; Zangrandi, Andrea; Schneider, Cyril (Frontiers in Pain Research, 2021)
Objective. The complex regional pain syndrome (CRPS) is characterised by brain changes that are not addressed yet by conventional treatment regimens. Repetitive peripheral magnetic stimulation (rPMS of muscles) is painless and noninvasive and it can influence these changes (induction of brain plasticity) to reduce pain and improve motricity. This open-label pilot study tested rPMS after-effects in CRPS on pain intensity and sensorimotor control of the upper limb, along with changes of the primary motor cortex (M1) excitability. Methods. Eight patients with CRPS were enrolled in a single session. Patients were tested at pre- and post-rPMS over the flexor digitorum superficialis muscle. The clinical outcomes were pain intensity, proprioception, active range of motion and grip strength. M1 excitability was tested using single and paired-pulse transcranial magnetic stimulation (TMS) of M1. Results. In our small sample, rPMS reduced instant and week pain, improved proprioception and range of motion, and reduced the hemispheric imbalance of several TMS outcomes. The more M1 contralateral to CRPS side was hyperactivated at baseline, the more pain was reduced. Discussion. This open-label pilot study provided promising findings for the use of rPMS in CRPS with a focus on M1 plastic changes. Future randomized, placebo-controlled clinical trials should confirm the existence of a causal relationship between TMS outcomes and post-rPMS decrease of pain. If confirmed, results will favor the development of personalized treatments of peripheral noninvasive neurostimulation in CRPS.